(untitled) (Scientific journal of the Fergana State University, 2025)
This article provides information on the history of the Department of Botany, Biotechnology, and Ecology, which was established as part of one of the first higher educational institutions in our republic, Fergana State University. The historical roots and stages of development of the department are inextricably linked with the history of the university. The department has trained highly qualified specialists not only for the Fergana Valley but also for various regions of Uzbekistan, as well as for a number of foreign countries. Special attention is given to its establishment, long-standing history, and current state, as well as the activities of teachers and mentors who are true devotees of science and education. The faculty of the department makes a significant contribution to the training of highly qualified educators, scientists, and leaders who selflessly work not only in educational institutions but also in various sectors of the national economy for the prosperity of our country.